Situation Report: Poland, 24 April 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Polish Delegation to the Karlovy Vary Conference Gomulka's Speech at Schwedt Economic Results of the First Quarter 1967 French Syndicate to Build Polish Fertilizer Factory Another Attack on Gomulka by Polish Rebel CP